Comovement of Greater China Real Estate Markets: Some Time Scale Evidence. Issue 3 (1st July 2019) - Liow, Kim Hiang; Zhou, Xiaoxia; Li, Qiang; Huang, Yuting
Abstract : The novelty of this study is the use of wavelets, which make it possible to assess simultaneously how the Greater China (GC) and international securitized real estate markets comove at various frequencies. From the wavelet analysis, investors can extract the time scale that most interests them. We apply both continuous wavelet coherency modeling and discrete decompositions to unveil the multi-horizon nature of the co-movement relationship. We find that the examined real estate market co-movement is a "multi-scale" phenomenon. The strength of the return linkage increases with scales. The co-movement within and across the three GC markets is unstable and the pattern of the relationship is non-uniform across various time scales. The strongest degree of cross-market connection occurs during the global financial crisis period and at the longest investment horizon of 256–512 days. Moreover, the real estate-stock returns of the three GC economies are less correlated in the long run, implying potential opportunities for both time and scale in GC real estate-stock portfolio diversification activities.